2018
DOI: 10.1159/000492153
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy with Biweekly Cetuximab: Optimizing Schedule Can Preserve Activity and Improves Compliance in Advanced Head and Neck Cancer

Abstract: Objectives: This study evaluates maintenance cetuximab administered every 2 weeks (q2w) after chemotherapy plus cetuximab as first-line treatment in a series of patients with head and neck squamous cell cancer and compares the results with those obtained in a historical control group of patients receiving weekly cetuximab. Methods: After chemotherapy plus cetuximab as first-line treatment, in Group A, 36 patients enrolled from October 2016 to November 2017, received biweekly cetuximab, administered at 500 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Recently, metronomic chemotherapy, using oral tegafur-uracil, has been reported to improve survival and reduce DM in stage III-IV OSCC treated by surgery or CCRT 41 , 42 . Cetuximab, a monoclonal antibody targeting epidermal growth factor receptor, has also been shown to be a tolerated and effective regimen for maintenance therapy in recurrent metastatic HNSCC 43 , 44 . Immune check point inhibitors, such as pembrolizumab for PD-L1 high OSCC, are another type of agents in ongoing clinical trials for maintenance adjuvant therapy in locally advanced HNSCC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, metronomic chemotherapy, using oral tegafur-uracil, has been reported to improve survival and reduce DM in stage III-IV OSCC treated by surgery or CCRT 41 , 42 . Cetuximab, a monoclonal antibody targeting epidermal growth factor receptor, has also been shown to be a tolerated and effective regimen for maintenance therapy in recurrent metastatic HNSCC 43 , 44 . Immune check point inhibitors, such as pembrolizumab for PD-L1 high OSCC, are another type of agents in ongoing clinical trials for maintenance adjuvant therapy in locally advanced HNSCC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Vargo et al (22) described how their treatment plan, which used target RT and took advantage of radiobiological benefits, resulted in a more effective regimen that delivered fewer large fractions, thereby reducing treatment time and acute toxicities compared to standard RT. Addeo et al (57) also supported the use of IT for treatment optimization, as they found that the use of maintenance IT after adjuvant IT and chemotherapy improved effectiveness, convenience, tolerance, and compliance with the treatment plan. However, further research is necessary to weigh the costs and benefits of optimizing treatment.…”
Section: Discussionmentioning
confidence: 94%
“…In patients with recurrent or metastatic HNC, prior to the advent of immunotherapy, the addition of cetuximab to first-line platinum (cisplatin or carboplatin) and 5-fluorouracil chemotherapy and the continuation of cetuximab as maintenance therapy in the case of tumor response or disease stabilization significantly improved overall survival (OS), progression-free survival (PFS), and response rate (RR) (3). Maintenance therapy with simplified biweekly (instead of weekly) cetuximab is a safe, effective and feasible alternative therapy in these patients (4,5).…”
Section: Introductionmentioning
confidence: 99%